International Organization’s Approach to The Problems of Governing Globalization - Mohammed Ali Ahmed (QALAAI ZANIST SCIENTIFIC JOURNAL, 2024)
Global governance is one of the major phenomena of the world politics; however, approaches to tackle the problems of global governance or governing globalization are approved or verified by all sides. The main question of the current research is: Do International Organizations have an agreed approach for the problems of governing globalization or global governance? Despite that the states and in somehow the international organizations are part of the problems, however, one of the approaches to deal with global governance is international organizations. This study uses the comparative approach and document analysis. This part analyses the relevant articles and documents which have articulated internationally to deal with the problems of global governance. This research is an effort to analyze the role of the international organization’s approach to the problems of governing globalizations. There have been many problems in the world, thus this research is unable to emphasis on all of them. It would be concluded that the international organization’s approach to deal with the problems of governing globalization is not adequate and poses shortcomings. In addition, the international organizations are unable to have an approach upon-agreed on to deal with the challenges which the humanity is facing.